Exploring Logistics Strategy in Malaysian SMEs Performance - Ramasary, Ravi; Mohd Saifudin, Adam; Shamsuddin, Jauriyah (ExcelingTech Publishers, 2020)
To strengthen the SMEs development, SMEs are measured as one of the essential elements to enhance country’s economic performance, creating employment opportunities and transforming towards industrialized country by the year 2050. However, in order to sustain role of contributing to the mainstream economy, SMEs have to implement effective strategies in all of their business operations, inclusive of logistics. Therefore the objective of this study was to investigate the challenges encountered as well as the benefits realized by SMEs during the implementation of logistics strategies. The finding of the study reveal that, the lack of logistics management skills among the workforce were the most important challenges to SMEs. In this studies, quantitative approach method was conducted to gather data in the study to measure the descriptive statistics of all the constructs been measured in the survey. This paper will first discuss the literature review covering four areas that are important in this study. This will be followed by finding, recommendations as well as the conclusion of the studies